2020
DOI: 10.15252/emmm.201911622
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of transcription by dactinomycin reveals a new characteristic of immunogenic cell stress

Abstract: Chemotherapy still constitutes the standard of care for the treatment of most neoplastic diseases. Certain chemotherapeutics from the oncological armamentarium are able to trigger pre-mortem stress signals that lead to immunogenic cell death (ICD), thus inducing an antitumor immune response and mediating long-term tumor growth reduction. Here, we used an established model, built on artificial intelligence to identify, among a library of 50,000 compounds, anticancer agents that, based on their molecular descrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
55
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 75 publications
1
55
0
Order By: Relevance
“…Intrigued by this observation, we used multiple tests to measure RNA synthesis (and downstream protein synthesis, downstream of RNA transcription) to conclude that most ICD inducers (including anthracyclines, oxaliplatin, lurbinectedin, crizotinib and thiostrepton) actually cause an inhibition of DNA-to-RNA transcription (and hence a subsequent inhibition of RNA-to-protein translation) and that this effect may cause a peculiar ER stress response consisting in the phosphorylation of eIF2α by eIF2α kinase 3 (EIF2AK3, better known as PERK) without any other signs of the unfolded stress response such as activation of the ATF6 and the IRE1-XBP1 axes. [8][9][10] The aforementioned results suggest that a vast class of ICD inducers (with the exception of microtubular poisons such as vinca alkaloids and taxanes) is able to reduce RNA synthesis, which resembles a response to viral infection. This has two major implications.…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…Intrigued by this observation, we used multiple tests to measure RNA synthesis (and downstream protein synthesis, downstream of RNA transcription) to conclude that most ICD inducers (including anthracyclines, oxaliplatin, lurbinectedin, crizotinib and thiostrepton) actually cause an inhibition of DNA-to-RNA transcription (and hence a subsequent inhibition of RNA-to-protein translation) and that this effect may cause a peculiar ER stress response consisting in the phosphorylation of eIF2α by eIF2α kinase 3 (EIF2AK3, better known as PERK) without any other signs of the unfolded stress response such as activation of the ATF6 and the IRE1-XBP1 axes. [8][9][10] The aforementioned results suggest that a vast class of ICD inducers (with the exception of microtubular poisons such as vinca alkaloids and taxanes) is able to reduce RNA synthesis, which resembles a response to viral infection. This has two major implications.…”
mentioning
confidence: 97%
“…On one hand, it is possible to consider anticancer agents with known transcription-inhibitory properties as candidates for ICD induction. 9 On the other hand, it is relatively easy to measure inhibition of RNA synthesis in vitro, on cultured cells, for example using a chemically derivatized uridine analogue whose incorporation into nascent RNA, can be visualized by click chemistry to yield a fluorescent signal (Figure 1a). An alternative method to diagnose stalled transcription consists in detecting the separation of two proteins involved in RNA synthesis, nucleolin and fibrillarin, that normally (when RNA synthesis is active) colocalize in the nucleus, yielding an overlapping immunofluorescence staining (Figure 1b).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This intravenously administered cytotoxic antibiotic acts by intercalation to DNA and interruption of RNA transcription ( Hollstein, 1974 ; LiverTox, 2012). Recently, dactinomycin was shown to induce immunogenic cell death, suggesting a direct antineoplastic activity enhanced by immunomodulatory properties ( Humeau et al 2020 ). In fact, this drug is used in combination with other cytotoxic drugs in the management of a broad array of solid malignancies, such as gestational trophoblastic disease, Wilms tumor and Ewing sarcoma ( Li et al 2018 ; Alazzam et al 2016 ; van den Heuvel-Eibrink et al 2017 ; Gaspar et al 2015 ).…”
Section: Potential Anticancer Drugs For Covid-19mentioning
confidence: 99%
“…2 Recently, the inhibition of DNA-to-RNA transcription by cytotoxic drugs was described as a cardinal mechanism governing ICD. 3 Several preclinical studies have shown that ICD induced by chemotherapy or radiotherapy sensitizes to subsequent immunotherapy. 4 Thus, ICD induction with oxaliplatin and cyclophosphamide sensitized non-small cell lung cancers (NSCLC) expressing oncogenic Kras and lacking Trp53 to anti-CTLA-4 and anti-PD-1-mediated double ICB.…”
mentioning
confidence: 99%